2018
DOI: 10.1021/acs.inorgchem.8b00525
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sugar: A Green Assistance To Efficiently Exfoliate Inorganic Layered Nanomaterials

Abstract: We have demonstrated that natural sugars can efficiently exfoliate inorganic layered nanomaterials with direct stirring. The representative transition-metal dichalcogenides (MoS and WS), transition-metal oxide (MoO), and graphene were explored, and the formation of ultrathin nanosheets was verified. Glucose and MoS selected each other as the perfect partner with superior exfoliation and excellent properties. The obtained inorganic layered nanosheets possess favorable stability and dispersity, which renders it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Very recently, Chen et al prepared glucose/MoS 2 composite and observed high dispersity and stability of MoS 2 nanosheets in water for 20 days. 41 They ascribed the observation to interaction between glucose molecules and MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Chen et al prepared glucose/MoS 2 composite and observed high dispersity and stability of MoS 2 nanosheets in water for 20 days. 41 They ascribed the observation to interaction between glucose molecules and MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these observations, we suggest that adsorption of the sugar hydrates on the nanosheets’ surface might also account for their high stability over the investigated time period. Very recently, Chen et al prepared glucose/MoS 2 composite and observed high dispersity and stability of MoS 2 nanosheets in water for 20 days . They ascribed the observation to interaction between glucose molecules and MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2D materials successfully synthesized by mechanical exfoliation, an increasing number of synthetic methods, like chemical exfoliation and chemical vapor deposition (CVD) methods, have been developed to obtain 2D materials with various nanostructures. For example, there are more opportunities to obtain 2D materials with high crystallinity but small‐scale production through mechanical exfoliation method; chemical exfoliation methods such as electrochemical and solvents assistance exfoliation are apt to realize large‐scale production of 2D materials but without precise control of lateral size and thickness; and chemical vapor deposition method can form monolayer 2D materials and is also suitable for their wafer‐scale synthesis . Thanks to the synthetic variety of 2D materials, a wide variety of building blocks and techniques are applied to fabricate 2D/2D heterostructures.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Since the first synthesis of graphene (GR) with astonishing properties in 2004, “2D materials,” especially the atomically layered ones, as a new class of materials attracted great interest among researchers and simultaneously enormous efforts for the study and development of alternative layered materials. It has been demonstrated that ultrathin 2D materials possess unique physical, chemical, and electric properties, which are usually very different from those of their bulk counterparts, e.g., large specific surface area, excellent bendability, unique optical bandgap structures, strong light–matter interactions, and high carrier mobility. Furthermore, most 2D nanosheets are easily fabricated into flexible films with uniform thickness, which are programmable platforms for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of graphene with layered structure has aroused global research interest in two-dimensional (2D) nanostructures owning to their unique crystallographic structure, compelling physical and chemical properties and promising applications in the fields of electronics, photonics, photoelectronic devices, chips, catalysis, and so on. Typically, graphene and all the graphene-like 2D materials, such as transition metal dichalcogenides (MoS 2 , MoSe 2 , WS 2 , WSe 2 , etc. ), h -BN, and InS, among others, are bonded with weak van der Waals’ force in interlayers, which enables an easy peeling off from their bulks. Hence, it is easy to achieve monolayer or few atomic layers featured ultrathin 2D nanosheet morphology through mechanical cleavage, sonication-assisted liquid exfoliation, ion-exchange-assisted liquid exfoliation, and so forth. However, for the structurally nonlayered materials, it is extremely challenging to obtain the layered nanosheets using the above-mentioned methods due to the strong interlamellar force of chemical/covalent bond and the structural instability arising from unsaturated dangling bonds. Therefore, it is technologically important and essential to develop some feasible and universal synthesis strategies for the growth of 2D nanosheets without intrinsic layered structures.…”
Section: Introductionmentioning
confidence: 99%